Design and Implementation of 12-Bit Arithmetic Logic Unit with 8 Operation Codes to Field Programmable Gate Array - Sumari, Arwin Datumaya Wahyudi; Hijriana, Sukriya; Dermawan, Denny (Faculty of Engineering, Universitas Tanjungpura, 2023)
Digital system has been a part of human life since the invention of the computer with a microprocessor as the central brain. At the heart of a processor is an Arithmetic Logic Unit (ALU) that handles arithmetic and logic operations. The need for high-speed computation to handle complex computations demands microprocessors with higher performance. The existing 4-opcode 8-bit ALU cannot handle multiplication operations, so a solution is needed. In this research, while raising the appeal of beginners, a 12-bit ALU with eight operation codes (opcode) was designed and implemented in Xilinx